Integration of Islamic education with science and technology in Islamic junior high school - Bekti Taufiq Ari Nugroho (Prodi PGMI IAIN Salatiga, 2017)
AbstractThe integration of Islamic education with learning of science and technology is expected to be meaningful and easily understandable so that the goal of Islamic education in leading the students to recognize, understand, contemplate, believe, be piety, and have noble character in implementing the teachings of Islam from the primary source i.e. the holy book of Al-Quran and Al-Hadith through the teaching guidance, practicing, and the use of experience can be accomplished. The key of the integration in controlling and restoring science and technology to its original position, namely: amar ma'ruf, nahi munkar, and having faith in God. This study aims to determine the integration of Islamic education with science and technology in SMP Islam Al-Azhar 21 Solo Baru. By using qualitative descriptive method and also through triangulation technique to test the validity of data, the study is also aimed to search and arrange systematically the data obtained. The data is taken from interviews, field, and documentation by organizing data into categories, describing them into units, synthesizing, preparing into the pattern, classifying the important things that will be learned, and then making a conclusion. From the results of the study, it can be concluded that the observation result of creativity of the students showed that the smooth aspect of the students who have excellent category is 41.28% and the results of the flexibility aspect of the students who have excellent category is 36.69%. The observation results indicate that the detail aspect of the students who have excellent category is 33.98%.Keywords: Islamic Education, Science, Technology AbstrakIntegrasi pendidikan agama Islam dengan sains dan teknologi pembelajaran yang dilaksanakan diharapkan menjadi lebih bermakna dan mudah dipahami. Sehingga tujuan pendidikan agama Islam dalam mengarahkan peserta didik untuk mengenal, memahami, menghayati, hingga mengimani, bertaqwa, dan berakhlak mulia dalam mengamalkan ajaran agama Islam dari sumber utamanya yaitu kitab suci Al-Quran dan Al-Hadits, melalui kegiatan bimbingan pengajaran, latihan, serta penggunaan pengalaman dapat terlaksana. Kuncinya dalam mengendalikan dan mengembalikan sains dan teknologi ke posisi semula, yaitu: amar ma’ruf, nahi munkar, dan iman kepada Allah. Penelitian ini bertujuan untuk mengetahui integrasi pendidikan agama Islam dengan sains dan teknologi di SMP Islam Al-Azhar 21 Solo Baru. Dengan menggunakan metode deskriptif kualitatif, melalui teknik triangulasi untuk menguji keabsahan data, yaitu mencari dan menyusun secara sistematis data yang diperoleh dari hasil wawancara, lapangan, dan dokumentasi dengan cara mengorganisasikan data ke dalam kategori, menjabarkannya ke dalam unit-unit, melakukan sintesa, menyusun ke dalam pola, mengklasifikasikan hal-hal penting yang akan dipelajari kemudian membuat kesimpulan. Dari hasil penelitian disimpulkan bahwa: hasil amatan kreativitas pada peserta didik menunjukkan bahwa untuk aspek kelancaran pada peserta didik yang memiliki kategori baik sekali sebesar 41.28%. Hasil amatan menunjukkan bahwa untuk aspek fleksibilitas pada peserta didik yang memiliki kategori baik sekali sebesar 36.69%. Hasil amatan menunjukkan bahwa untuk aspek kerincian pada peserta didik yang memiliki kategori baik sekali 33.98%. Kata kunci: pendidikan Islam, ilmu pengetahuan, teknologi